Prototipe Aplikasi Manajemen Sparepart Atm Menggunakan Framework Zachman Pada Logistik Asp - Ridlan Ahmad (Jurnal Bangkit Indonesia, 2019)
ASP Logistics is a place for depositing ATM spare parts where one of the branches owned by the company is ASP Logistics in Ambon city. ATM spare parts management in Ambon ASP Logistics has good procedures for incoming data and outgoing spare parts for ATMs, but the system is still done manually such as reports typed in Microsoft Excel and also written on the Stock Request Form (SRF) work report. The research aimed to Prototype And Design of Management Information Systems for ATM Spare Parts at Ambon ASP Logistics. The analysis model in collecting data uses a SWOT analysis, while the EA Score card is a test of whether this system is feasible to use. And the design carried out using the Zachman Framework enterprise architecture and the UML approach Mapping of the Zachman Framework in this study is limited only to the perspective of the Planner, Owner and Designer while each column consists of Data (What), Function (How), Network (Where) , People (Who), Time (When) and Motivation (Why). The results of the analysis and design carried out, produced an ATM Spare Parts Management Information System model that can control all part activities optimally consisting of inventory data, part usage data, part entry data and data return (return) parts which are subsequently implemented in the form of a prototype as an illustration of the system interface to be built. By using the Zachman Framework enterprise architecture, detailed information is obtained about how the ATM spare parts management information system is designed, as well as all the needs of data, human resources and infrastructure that support the operation of the information system. Keyword: Keywords: Logistics, SWOT Analysis, EA Score card. Zachman Framework, UML, ATM Spare Parts Management